RANCANG BANGUN GAME EDUKASI HURUF HIJAIYAH SEBAGAI PEMBELAJARAN ANAK USIA DINI BERBASIS CONSTRUCT 2 - zalra; Nurgiyatna (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Learning Hijaiyah letters for early childhood education is still commonly carried out using conventional methods, such as books and whiteboards, which are often less effective in attracting children's attention during the learning process. Advances in technology have created opportunities for utilizing games as educational media to support a more engaging and enjoyable learning environment. This study developed an educational game for learning Hijaiyah letters using the Construct 2 game engine. The game is intended to serve as a learning medium to facilitate the educational process for early childhood students at TK IT Taruna Teladan. The development process employed the Waterfall-based Game Development Life Cycle (GDLC) method, which consists of several stages, including requirement analysis and identification, design, implementation, testing, and system maintenance. System testing was conducted using the Black Box Testing method to ensure that all features functioned according to their intended design, while the System Usability Scale (SUS) instrument was used to evaluate user responses and assess the application's usability from the users' perspective. The results of this study produced an educational game equipped with features such as Hijaiyah letter recognition, letter-matching games, pronunciation audio, sound settings, and a scoring system. Based on the evaluation results, the application was able to perform all its functions properly. The average System Usability Scale (SUS) score of 75, categorized as "Good," indicates that the game is suitable for use as a learning medium for teaching Hijaiyah letters to early childhood learners.